2017
DOI: 10.1590/1982-3703000012015
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de Vida e Valores nas Organizações: Impactos na Confiança do Empregado

Abstract: Resumo Os estudos sobre as relações empregado-organização são favorecidos pela compreensão de que recursos humanos são parte fundamental do processo organizacional. A confiança é um aspecto importante nesse processo, podendo influenciar a eficácia e o desempenho organizacionais. Assim, este estudo teve por objetivo verificar o poder de predição da percepção de valores organizacionais e da qualidade de vida no trabalho (QVT) sobre a confiança do empregado na organização. A amostra foi composta por 188 indivíduo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…According to some authors (Ferreira, 2011;Pracidelli & Rossler, 2018;Sant'Anna, Kilimnik, & Moraes, 2011), addressing the QWL is a challenge in the sense of differentiating it from its vulgarization, which confuses with organizational marketing, public relations strategies, self-help, assistance and/or compensatory programs (for example, offering work-based physical activities and additional payments for hazardous duty). However, fortunately, we recognized that there are scientific approaches (Hackman & Oldham, 1975;Mejbel, Almsafir, Diron, & Alnaser, 2013), including Brazilian researchers (Carvalho, Domingues-Júnior, & Sant'Anna, 2017;Ferreira, 2015;Sant'Anna et al, 2011;Silva & Oliveira, 2017). This does not mean that the tendency for organizations to use QWL programs with the intention of reconciling the interests of capital and labor has been overcome; this trend was considered by some authors (Padilha, 2010;Pracidelli & Rossler, 2018) as illusory and responsible for deepening the alienation of work.…”
Section: Quality Of Working Lifementioning
confidence: 99%
“…According to some authors (Ferreira, 2011;Pracidelli & Rossler, 2018;Sant'Anna, Kilimnik, & Moraes, 2011), addressing the QWL is a challenge in the sense of differentiating it from its vulgarization, which confuses with organizational marketing, public relations strategies, self-help, assistance and/or compensatory programs (for example, offering work-based physical activities and additional payments for hazardous duty). However, fortunately, we recognized that there are scientific approaches (Hackman & Oldham, 1975;Mejbel, Almsafir, Diron, & Alnaser, 2013), including Brazilian researchers (Carvalho, Domingues-Júnior, & Sant'Anna, 2017;Ferreira, 2015;Sant'Anna et al, 2011;Silva & Oliveira, 2017). This does not mean that the tendency for organizations to use QWL programs with the intention of reconciling the interests of capital and labor has been overcome; this trend was considered by some authors (Padilha, 2010;Pracidelli & Rossler, 2018) as illusory and responsible for deepening the alienation of work.…”
Section: Quality Of Working Lifementioning
confidence: 99%
“…However, studies have shown that health workers, including nurses, nursing assistants, physical therapists 5,[18][19][20][21][22] , doctors [22][23][24][25] , and administrative staff 3,4,11,26,27 , have varying perceptions of their own QWL.…”
Section: Introductionmentioning
confidence: 99%